Wage Compression, Employment Restrictions and Unemployment : The Case of Mauritius. (IMF Working Papers; Working Paper ;, 2004)
Governments often intervene in labor markets with the aim of reducing inequality and promoting employment. Such intervention often results in wage compression and restrictions on how firms use their workers. This paper investigates the impact of such interventions on the labor market conditions faced by low-skill workers in Mauritius. It finds that even relatively minor intervention can dramatically increase the fragility of jobs, the length of unemployment spells, as well as the extent of unemployment and labor market churning. With institutions of the type studied here common across many different types of countries, these results have relatively general implications.